The Impact of Using Multimedia Interactive Based for Learning Media on Teacher and Student Communication in Bandung - Marvin Chandra Wijaya (BBPSDMP KOMINFO MAKASSAR, 2019)
Communication between teachers and students today still uses many conventional systems. With the advancement of computer technology, especially in the field of multimedia, it can be used as an innovative learning media. Multimedia created is an interactive film that can be controlled by the user / audience. Interactive films that are made useful to learn basic component parts in a personal computer. Interactive films begin with the basic display of a personal computer. Then the images in the interactive film can be selected by the user/audience to choose the part they want to learn. How to explain the basic components of a computer can be made interactive and interesting, and is preferred by many people. To create a multimedia presentation you can use a markup language, called SMIL (Syncronized Multimedia Integration Language). SMIL is a recommendation from the World Wide Web Consortium (www.w3c.org). SMIL is the same markup language as HTML and is a variant of XML. From the results of the application in several schools and universities in the city of Bandung, yielding positive results. Motivation from students to listen to the lesson material given increases, this makes the absorption rate of the learning material tested by giving test questions make the students' grades increase.